Understorey birds of Cikaniki Research Station, Gunung Halimun-Salak National Park, West Java: Report of the Indonesian Bird Banding Scheme Training Programme - Noske, Richard; Prawiradilaga, Dewi M; Drynan, David; Leishman, Alan; Rutherford, William (KUKILA, 2011)
This report summarises findings from the first Training of Trainers (ToT) programme of the Indonesian Bird Banding Scheme (IBBS), which took place at Cikaniki Research Station (1000- 1100 m asl), Gunung Halimun-Salak National Park, during July 2009, and compares them with the results of previous banding studies conducted at the site by PPB-LIPI staff since 1996. Over the seven days from 13 to 19 July 2009, a total of 97 individuals representing 29 species were captured, and in most cases, banded. Juvenile birds belonging to 13 species comprised 28% of all individuals captured, and early primary moult was found on 32% of adults captured, suggesting that many species had recently completed breeding. The two most frequently captured species were the Little Spiderhunter Arachnothera longirostra and the Javan Fulvetta Alcippe pyrrhoptera. A comparison with previous banding studies between 1996 and 2002 at the same site shows that the latter species was repeatedly misidentified as the Fulvous-chested Jungle Flycatcher Rhinomyias olivacea, a species otherwise unknown for the park. This finding negates the conclusions of previous reports that R. olivacea is an important component of the understorey avifauna of the park at this altitude. Nine individuals, representing six species, were recaptured during the IBBS programme, including a Sunda Forktail Enicurus velatus that was at least 9 years old when re-trapped, and a Horsfield’s Babbler Malacocincla sepiaria that was at least 8.75 years old.